Penerapan Algoritma Prefix Code Pada Kompresi File Gambar - Esteria Novebri Simanjuntak (BEES: Bulletin of Electrical and Electronics Engineering, 2021)
Data compression is a way of changing data from a set of characters to be converted into a code with the aim of saving storage space. Along with the development of the era, the more advanced devices result in the resulting data size increasing and continuing to increase, if the data size is large it can cause waste of data storage space and waste of quota usage when sharing because it requires a technique to change the size of the data so that to be smaller. The author will apply how it works on image files. In this study, an application to reduce the size of an image file into an application with the Prefix code algorithm. The Prefix Code algorithm is a data compression algorithm that can compress image files with the aim of reducing the size of the data in the image. There are many types of methods or algorithms in image compression, but in this algorithm the writer only wants to know the compression process using the Prefix Code algorithm using the C1 code where the author has successfully compressed an image file with the prefix code algorithm using the C1 code has the ability to compress 37 image data, 5% in an image file